2017
DOI: 10.1097/cej.0000000000000238
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of human papillomavirus after introduction of HPV vaccination: a large population-based survey of Scandinavian women

Abstract: Using a large, population-based survey, we assessed the levels and correlates of human papillomavirus (HPV) awareness among Scandinavian women after introduction of HPV vaccination. In 2011-2012, a random sample of women aged between 18 and 45 years from Denmark, Sweden and Norway received a questionnaire on lifestyle, health and HPV awareness. We included 47 895 women (response rate 60.6%) in our study. Country-specific and age-specific proportions of women who had heard of HPV in 2011-2012 (postvaccination s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…Numerous previously reported surveys have demonstrated that 50% to 85% of women know about cervical cancer in Asia, 17,18 which is in accordance with the observations of our study. Human papillomavirus awareness was higher in Denmark (75.8%) and Sweden (74.8%) compared with Norway (62.4%) and Senegal (63%), 19,20 while studies from Yunnan, China (52.6%), Xinjiang, China (0.14%, 10 out of 7100), and Brazil (37%) have reported low levels of knowledge and awareness about HPV that are consistent with the findings of this study. 13,21,22 However, the levels of knowledge and awareness about HPV observed in the present study are higher than those in previously reported studies 13,23 but are still low.…”
Section: Discussionsupporting
confidence: 88%
“…Numerous previously reported surveys have demonstrated that 50% to 85% of women know about cervical cancer in Asia, 17,18 which is in accordance with the observations of our study. Human papillomavirus awareness was higher in Denmark (75.8%) and Sweden (74.8%) compared with Norway (62.4%) and Senegal (63%), 19,20 while studies from Yunnan, China (52.6%), Xinjiang, China (0.14%, 10 out of 7100), and Brazil (37%) have reported low levels of knowledge and awareness about HPV that are consistent with the findings of this study. 13,21,22 However, the levels of knowledge and awareness about HPV observed in the present study are higher than those in previously reported studies 13,23 but are still low.…”
Section: Discussionsupporting
confidence: 88%
“…As the knowledge of HPV and its vaccine is pivotal for HPV vaccine promotion [22], identifying the factors associated with awareness thereof is vital to effectively to raise awareness about HPV infection and the benefits of HPV vaccination among targeted populations. We identified predictors of HPV and HPV vaccine awareness that were concordant with findings reported in previous studies, namely age [18,20,23], education level [17-20,23-,25], income level [18,23], age at sexual debut [24] and number of sexual partners [23,24]. Being the mother of a daughter was also associated with high HPV awareness [20].…”
Section: Discussionsupporting
confidence: 86%
“…A previous study based on the "health belief model" (45) found that women's willingness to participate in HPV self-sampling was influenced by their perceived self-efficacy to take the sample correctly; their understanding of the link between HPV and cervical cancer; and their perception of the benefits of and barriers to self-sampling (46). Thus, our observation that women with low education were less likely to self-sample might be due to lower self-efficacy to perform self-sampling or lower awareness of the benefits of cancer screening (47,48). Moreover, socioeconomically disadvantaged groups and women with severe mental illness may experience a challenging everyday life, which could potentially result in decreased capacity to participate in preventive care, even when offered a free-of-charge and convenient screening method such as self-sampling.…”
Section: Potential Reasons For Nonparticipation In Self-samplingmentioning
confidence: 94%